The determinants of undergraduate CGPA among students' of the Faculty of the Social Sciences, University of Ibadan (2006)
This paper examines the determinants of students' performance in the University. We used the grade point average (GPA) of students in Faculty of the Social Sciences of University of lbadan as a model of characteristics of the students at the time of their entry into the university. This helps in identifying the factors that are likely to predict the successful outcome of the students in the university. Specifically, the research tests whether SSCE and JAMB scores are reliable predictors of GPA. In doing this, we analysed a sample of 866 students who graduated in three different sessions from five departments in the faculty. The results of our analysis suggest that while the performance in the General Certificate of Education, ordinary level examinations appears to better predict undergraduate performance as measured by CGPA, JAMB scores are not good predictors of students' grades in the faculty.